Incidence, prevention and treatment of migraine - Alsaaid, Maan; Alowaa, Zainab; Abufaia, Rawan; Rukun, Rana; Saddeek, Aisha; Alnassir, Mohammed; Lamfon, Mohammed; Mohmmed, Ayah; Bazhair, Njood; AlNouri, Afnan (International Journal Of Community Medicine And Public Health, 2018)
Migraine is the second most common type of headache worldwide. It is estimated to affect about one sixth of population. Despite being a primary headache, it is severe, incapacitation, and disturbing normal daily life activity. Therefore, researchers and neuroscientists were and are still endeavouring to understand the basic mechanisms of migraine and its preventive strategies. Treatment of migraine is also a subject of continuous interest. Prevention of migraine is the cornerstone of migraine management. It is achieved by reducing exposure to risk factors, prophylactic treatment of recurrent migraines, and acute treatment prior to exposure to precipitating factors. Treatment of migraine refers to the acute management of headaches when they occur. Many medications are available for abortion or relief of headache, and the choice of which depends on many factors such as the patients' comorbidities, the headache characteristics and severity, the associated symptoms, the adverse events, and the patients' preferences. This article will review and discuss the incidence of migraine, its preventive measures, and treatment updates.